Development of an automatic system for helicopter approach to a moving vessel - Bibik, P.; Topczewski, S.; Żugaj, M. (My University, 2018)
The paper presents part of the results obtained in the HELIMARIS project ("Modification of an optionally piloted helicopter for maritime mission performance") led by PZL Swidnik in cooperation with Warsaw University of Technology and CTO. In the paper, development of control algorithms for automated approach of a light single rotor helicopter to the moving vessel is presented. For the purpose of the approach task a Linear Quadratic Regulator (LQR) is used. The model of a helicopter is developed and evaluated in FLIGHTLAB software using flight test data for validation. Developed solutions and cases for approach of the helicopter to the vessel are presented and discussed.